IDENTIFIKASI MISKONSEPSI MENGGUNAKAN TES DIAGNOSTIK THREE-TIER PADA HUKUM NEWTON DAN PENERAPANNYA - Anna Shalihah; Diah Mulhayatiah; Fathiah Alatas (Journal of Teaching and Learning Physics, 2016)
This research aims to identify misconceptions that occur in Newton's law and its application based on diagnostic test results of students of class X SMAN 6 Tangerang Selatan and show sub concepts that experienced the highest misconceptions and low. The research was conducted in October 2015 - January 2016. The research method used is descriptive-quantitative. This study was conducted in two stages: stage manufacture of instruments held in SMAN 6 and 4 Tangerang Selatan and the implementation phase of the research conducted at SMAN 6 Tangerang Selatan. The instrument used is a three-tier diagnostic test. Results obtained 20 questions about the making of a valid with validity 0.64 and reliability 0.78. Results of the discussion showed misconception that occurred at 32.50% with a false positive at 20.97% and false negative amounting to 11.67% and misconceptions highest in subconcepts legal principles III Newton with a percentage of 56.92% and the lowest in the subconcepts variety of force with a percentage of 24.08%.